A Clinical Study to Evaluate the Effect of Pathyadi Kwatha and Anu Taila Nasya in the Management of Ardhavbhedaka w.s.r. to Migraine (AYUSHDHARA, 2025)
A rise in acute and chronic health issues is caused by the shifting demands of the workplace, especially in light of urbanization and contemporary lifestyles. A large percentage of people suffer from migraines, one of the most prevalent and debilitating chronic illnesses. Migraines are not life-threatening, but it can significantly affect day-to-day functioning. People who suffer from migraines face not only agonizing pain, but often experience social isolation, disrupted personal relationships, and discrimination at work. In Ayurveda clinical features of Ardhavabhedaka resembles to the symptoms typically associated with migraine, including intense, one sided headache. Treatment modality which are currently available in modern medicine are also not satisfactory and are financially burdensome for many patients. Migraine is managed generally with NSAIDS’s and analgesics drugs which give only short term relief and pain may rebound. The purpose of this study was to find out an effective and well accepted drug with minimal or no complications for this illness. 50 patients who were diagnosed with Ardhavabhedaka w.s.r. migraine were allocated randomly into two groups. The trial drug i.e., Pathyadi Kwatha 50ml twice a day was given to 25 patients of Group I and trial drug Pathayadi kwath 50ml and Anu tail Nasya was given to 25 patients of group II. Pathyadi Kwath decoction has ingredients having Ushana Virya and Vatshamak properties, which may be useful in management of Ardhavbhedaka and Anu Taila have the property of Tridoshaghnta and Snigdha guna. Subjective parameters were assessed before and after the completion of trial. Data obtained during the trial was tabulated and statistically analysed.